A participação política, entre o debate e a visibilidade: um estudo de mídia e cidadania, a partir de Hannah Arendt e Habermas - BOARATTI, André (2009)
The issue of political participation, usually used in Political Science, acquires a new approach from the Social Comunication point of view. Its important to point that the theoretical reference used in the study, were the contributions of Habermas and Arendt concepts about public sphere. According to this sense, political participation is located in the communicative action in public spaces of speaks for free and equal citizens. The agents start to became equal in the moment that all arguments are provided, so it can be say that citizenship is a dialogical process of construction of public spaces, that the main function is not only the social function of pressing the representative power, but mainly to serve as a basis for democratic institutions. The concept of power according to Arendt replaces the importance of political participation as a sufficient condition for democracy. The question now is to know what is the real paper of the media in the build process of democracy guided by citizen participation. First its important to mention that the term "means" of communication had been replaced by the term "communication institutions" because they do not behave as mere transmitters of content, but they are actors in social relations, first of all. The atomistic effects of communication institutions reporting about people are relativized in the moment that it takes into account the importance of the interpretation of media messages in the receiving reception. This process occurs often times in family environments homes, in private atmosphere. The passive citizenship according to this sense, occurs in the private space, in the moment that these people have born , they are able to receive from the Estate the condition of citizens. The only citizenship goes beyond the normative assumption when people have possession of the information responsible for mobilizing public opinion. The formation of the general opinion not only occurs in public places, but mainly in the private sphere in which the television media is still the main source of information for citizens. The condition for the citizenship becomes active in the public space of speech, is the reception. However, the citizens as audience, influence the production of the media contents, through a process of awareness undertaken by social actors, for example, the campaign "Who is financing the plummet is against citizenship", provide by the Commission Human Rights and Minorities of the Chamber of Deputies. Through the action of these social organizations, the passive citizens , inside their home,start to get a selective criterion to guide the process of reception. Therefore, the political participation it starts not only in public sphere, but in private atmosphere of the home, during the reception of media content. Acording to this line of tought, the political participation can do the function of the key central to think about the relationship between media and citizenship, that is, how far does the limit of one and another, and how both of them contribute to a democracy not only as a political power, but as a form of social life